INVENTARISASI DOMINANSI GULMA DI KEBUN PERCOBAAN WATU ALO, NUSA TENGGARA TIMUR - Dumaris Priskila Purba; Zulfa Az Zahroh; Dini Sundari; Elfrida Knaofmone (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2025)
Weed inventory is important to assess the potential for the development of crop cultivation within a specific land area. This study aims to identify weed species and determine weed dominance in the experimental field at Watu Alo, Manggarai, East Nusa Tenggara. A purposive random sampling technique was conducted using the quadrat method, in which 1 x 1 m2 plots were randomly thrown across the field and repeated five times. A descriptive analysis approach was used, with species identification based on morphological characteristics. The important Value Index and weed dominance values were subsequently calculated. The study revealed three major weed groups there are grasses (4 species), sedges (2 species), and broadleaf weeds (4 species). The most dominant weeds in that area were Ageratum conyzoides (143.5%).